Implementasi Protokol TCP/IP dalam Meningkatkan Efisiensi Transfer Data - Satriani Satriani; Dewi Andriany; Rusmawati Rusmawati; Mima Mima; Masnur Masnur; Salwana S; Ketrin Rinayanti Manullang (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The Transmission Control Protocol/Internet Protocol (TCP/IP) protocol is a crucial foundation for modern computer network communication interactions, enabling structured and reliable data transfer. This study aims to evaluate the application of TCP/IP to improve data delivery efficiency across a variety of network environments, including local area networks (LANs) and wide area networks (WANs). Through a systematic literature review and comparative analysis, this study investigates how TCP/IP works, the elements that influence transmission efficiency, and optimization methods that can be applied to improve network performance. The study's findings reveal that data delivery efficiency is significantly influenced by TCP window size settings, congestion control algorithms, and network infrastructure conditions. Proper TCP/IP implementation, including adjustments to parameters such as window size, can significantly reduce latency and dramatically increase throughput. The study also demonstrates that the choice between TCP and UDP should consider the nature of the application and data reliability requirements. The study's conclusions provide practical advice for network administrators and system developers on improving data delivery performance through efficient TCP/IP protocol configuration. These findings have a significant impact on the development of more efficient and responsive networks to meet today's data transmission demands